(untitled) (Annals of Medical Research, 2023)
Aim: In the present study, it was aimed to contribute to the literature in the light of reliable and accurate information by revealing in-hospital mortality rate, tumors’ pathology and location and whether they are of primary-metastasis or recurrence, initial admission complaint, type of admission, and demographic characteristics such as sex and age and in patients who were operated due to brain tumor. Materials and Methods: This retrospective study was designed with the inclusion of patients over the age of 18 years who applied to Tokat Gaziosmanpaşa University Neurosurgery clinic from the emergency department or outpatient clinic between January 01, 2017 and December 31, 2021, and who were hospitalized with a pre-diagnosis of intracranial mass and operated. Results: The most frequently seen tumors according to pathology results were metastasis with 27 (28.4%) patients. It was observed that the admission GCS (Glasgow Coma Scale) score of the deceased patients were significantly lower than that of the survivors (p = 0.042). Similarly, clouding of consciousness (p = 0.003) and GCS (p < 0.001) values were statistically significantly lower in the patients who were hospitalized from the emergency department. The length of hospital stay was longer in the deceased patients than in the survivors (p < 0.001). It was also observed that the patients with tumors located in the parietal lobe had longer hospital stay than the others (p < 0.001). Conclusion: The etiology of the patients indicated that the majority of metastases were originated from lung cancer (LC). We assumed that these patients would not have brain metastases in the absence of LC cancer. Eliminating the preventable factors that are in the etiology of LC cancer such as smoking would reduce the occurrence of mortality and neurological sequelae, and also economic-arse losses due to complex treatments of those conditions.